Potensi Telenursing Sebagai Inovasi Untuk Meningkatkan Kualitas Hidup Pasien Diabetes Melitus Tipe 2: Literature Review - MOCH. MAFTUCHUL HUDA; Saeful Biantoro; M. Dodik Prasetyo (STIKES dan AKZI Karya Husada Kediri, 2022)
Diabetes Mellitus Type 2 (DMT2) is a health problem of concern in Indonesia because it is a chronic disease with severe advanced complications and high mortality with a prevalence from 6.9% in 2013 to 8.5% in 2018. Uncontrolled blood sugar (glucose) levels in the blood can cause functional disorders like physical, psychological, and social dysfunction which can cause sufferers to feel less prosperous and result in a decrease in their quality of life. The use of telenursing technology is needed to optimize health services to improve the quality of life of DMT2 patients. This study aimed to determine the effectiveness of telenursing as a technological innovation to improve the quality of life of DMT2 patients. The literature study design used the research method sourced from the Sciencedirect, Ebscohost, Proquest, and Pubmed databases. Articles were screened based on the inclusion criteria of the study. Articles are subject to a feasibility process based on the Scimago Journal Rank and the Joanna Briggs Institute (JBI) instrument. Articles were analyzed based on the PICO method (Population, Intervention, Compare, Outcome) and grouped by Thematic Analysis. From the literature study conducted, several studies report that telenursing is proven to be effective in improving the quality of life of DMT2 patients. Education for DMT2 patients is carried out to increase patient knowledge so that they can control blood sugar (glucose) levels in the body, minimize the risk of complications, improve treatment capabilities and improve patients quality of life. The use of technology as innovation is needed for the efficiency of nursing services in the form of telenursing so that it can be a solution in improving the quality of life of DMT2 patients. Studies on technological developments that have the potential to improve the quality of nursing care, one of which is telenursing, can be optimized as an effort to improve the quality of life of DMT2 patients.